The influence of Arab parties on Israeli government policies and their balance toward Arab society The United Arab List a model - Rayan, Kamel Ahmad (Journal of Economic, Administrative and Legal Sciences, 2022)
In all the political crises that afflicted Israel in the past seven decades, Partisan political disagreements and rivalries were the most influential reasons for the collapse of governments. This was the reason for holding four electoral cycles in less than two years, up to the March 2021 elections, in which the Arab parties won ten parliamentary seats. This is due to the division of the Arab political forces into two lists; the Joint Arab League, with its three components, got six seats, and the United Arab League got four seats. This is in light of the decline of the strength of the Arab parties inside the occupied Palestinian territories 1948. And the absence of the ability to promote Arab voices and motivate them to participate, which reflects the gap between the expectations of the Arab public in Israel and the ability to address the accumulated problems it suffers from, including economic, social, service, as well as security, after the spread of crime in the Arab sector. It made them lose confidence in their weight and their ability to influence making the decision in Israel, and the decline of national agendas and the failure to take a strong position on the Israeli right Where it recorded low Arab participation, reaching (45%), which is the lowest Arab participation rate since the start of the Knesset elections in 1949. Accordingly, this research aims at a socio-political-economic reading of the participation of the United Arab List headed by Representative Mansour Abbas, affiliated with the Islamic Movement, “the southern wing” in the government coalition. That was established in Israel By studying the results and gains that will be achieved by entering the government coalition in an unprecedented step in the history of Arab-Israeli politics. It is essential to evaluate this experience and identify its risks, problems, and chances of survival, although it is still at the beginning with the aim of presenting general recommendations to the Arab parties inside the Palestinian territories 1948, to raise the levels of their internal coordination to activate the chances of their influence on public government policies, especially in the economic and social aspects that can decrease the severity of the living conditions of the Arab community, which as a result may enable it to influence the political scene and establish their survival on their land within the framework of their civil rights.